Designing and compiling parallel aligned corpora: pitfalls and (some) solutions on the example of a corpus of translated musem texts (English-Spanish) - Jorge Leiva Rojo (Revista de Lingüística y Lenguas Aplicadas)
Text corpora are tools having both a long tradition in research and a variety of applications. Of all existing types, this paper focuses specifically on parallel, aligned corpora. By taking one of this corpora as a starting point—a parallel, aligned corpus from museum texts originally written in English and subsequently translated into Spanish—, the aim of this article is to propose a methodology that consists of four basic stages. By the revision of previous literature on the topic, and by using multiple software programs—proprietary and free, specifically created for corpus compilation and created for other purposes—, it is concluded that, although the compilation of corpora such as the one that was intended is a feasible task, the procedure is full of obstacles. Some obstacles were overcome, while some were not; that is the case, for example, of the repetitions on the aligned corpus, which are not present in the corpus.